2020
DOI: 10.18203/2349-2902.isj20204990
|View full text |Cite
|
Sign up to set email alerts
|

Serum calcium slope is a predictor of post-thyroidectomy hypocalcemia

Abstract: Background: Hypocalcemia is a common complication following thyroidectomy. The effects of hypocalcemia can range from simple numbness to life-threatening seizures. Barring stridor, haemorrhage and hypocalcemia, other complications of thyroidectomy are not seriously morbid and hence patients can be sent home. This study sought to determine whether early postoperative calcium levels can predict hypocalcemia following thyroidectomy, to help decide on early discharge.Methods: This was a prospective cohort study, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In two studies carried out by Essa et al, (2021) and Vasudev & AV, (2020), the calcium curve that was always positive or initially negative and later positive in the first 24 hours after surgery indicated a low probability of manifestations of hypocalcemia (Essa et al, 2021;Vasudev & AV, 2020). Vasudev & AV, (2020) concluded that a stable or rising calcium curve ensures safety for patients undergoing total thyroidectomy on the first postoperative day to be discharged, as they do not present a risk of hypocalcemia (Vasudev & AV, 2020).…”
Section: Calcium Cut-off Valuementioning
confidence: 99%
“…In two studies carried out by Essa et al, (2021) and Vasudev & AV, (2020), the calcium curve that was always positive or initially negative and later positive in the first 24 hours after surgery indicated a low probability of manifestations of hypocalcemia (Essa et al, 2021;Vasudev & AV, 2020). Vasudev & AV, (2020) concluded that a stable or rising calcium curve ensures safety for patients undergoing total thyroidectomy on the first postoperative day to be discharged, as they do not present a risk of hypocalcemia (Vasudev & AV, 2020).…”
Section: Calcium Cut-off Valuementioning
confidence: 99%